Cellular and Humoral Immunity to SARS‐CoV‐2 Infection in Multiple Sclerosis Patients on Ocrelizumab and Other Disease‐Modifying Therapies: A Multi‐Ethnic Observational Study. Issue 6 (1st April 2022) - Kister, Ilya; Patskovsky, Yury; Curtin, Ryan; Pei, Jinglan; Perdomo, Katherine; Rimler, Zoe; Voloshyna, Iryna; Samanovic, Marie I.; Cornelius, Amber R.; Velmurugu, Yogambigai; Nyovanie, Samantha; Kim, Joseph J.; et al.
Abstract : Objective: The objective of this study was to determine the impact of multiple sclerosis (MS) disease‐modifying therapies (DMTs) on the development of cellular and humoral immunity to severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2) infection. Methods: Patients with MS aged 18 to 60 years were evaluated for anti‐nucleocapsid and anti‐Spike receptor‐binding domain (RBD) antibody with electro‐chemiluminescence immunoassay; antibody responses to Spike protein, RBD, N‐terminal domain with multiepitope bead‐based immunoassays (MBI); live virus immunofluorescence‐based microneutralization assay; T‐cell responses to SARS‐CoV‐2 Spike using TruCulture enzyme‐linked immunosorbent assay (ELISA); and IL‐2 and IFNγ ELISpot assays. Assay results were compared by DMT class. Spearman correlation and multivariate analyses were performed to examine associations between immunologic responses and infection severity. Results: Between January 6, 2021, and July 21, 2021, 389 patients with MS were recruited (mean age 40.3 years; 74% women; 62% non‐White). Most common DMTs were ocrelizumab (OCR)—40%; natalizumab —17%, Sphingosine 1‐phosphate receptor (S1P) modulators −12%; and 15% untreated. One hundred seventy‐seven patients (46%) had laboratory evidence of SARS‐CoV‐2 infection; 130 had symptomatic infection, and 47 were asymptomatic. Antibody responses were markedly attenuated in OCR compared with other groups ( p  ≤0.0001). T‐cell responses (IFNγ) were decreased in S1P ( p  = 0.03), increased in natalizumab ( p  <0.001), and similar in other DMTs, including OCR. Cellular and humoral responses were moderately correlated in both OCR ( r  = 0.45, p  = 0.0002) and non‐OCR ( r  = 0.64, p  <0.0001). Immune responses did not differ by race/ethnicity. Coronavirus disease 2019 (COVID‐19) clinical course was mostly non‐severe and similar across DMTs; 7% (9/130) were hospitalized. Interpretation: DMTs had differential effects on humoral and cellular immune responses to SARS‐CoV‐2 infection. Immune responses did not correlate with COVID‐19 clinical severity in this relatively young and nondisabled group of patients with MS. ANN NEUROL 2022;91:782–795